High photocatalytic performance of hydrogen evolution and dye degradation enabled by CeO2 modified TiO2 nanotube arrays. (15th February 2022) - Hou, Junwei; Yang, Hedong; He, Boyao; Ma, Jingui; Lu, Yuan; Wang, Qingyao
Graphical abstract: Highlights: The deposition of CeO2 on TiO2 NTs was achieved by solvtoerhmal/annealing treatment. The TiO2 NTs/CeO2 photoelectrode displayed the amazing photocatalytic capacity. The preparation and photocatalytic mechanisms were explored. Abstract: The environment remediation and new energy development are the investigation focus of scientists, and the photocatalytic technology could simultaneously achieve the goal by solar energy conversion. In this paper, the hybrid photocatalysts were synthesized by the deposition of CeO2 nanospheres on TiO2 nanotube arrays (TiO2 NTs) by the solvothermal/annealing treatment, and the operation order displayed vital influences on the photocatalytic capacity. The Sample 4 prepared with annealing-solvothermal-annealing treatment showed the improved light response and low photoelectron recombination. The high visible light-driven photocurrent and hydrogen generation were obtained, and the photocatalytic removal of RhB, MB and Cr(VI) was also attractive. The hybrid TiO2 NTs/CeO2 photocatalyst displayed the high photostability toward the H2 generation and dye degradation, and the mechanism was proposed to explain the outstanding photocatalytic ability. Consequently, it could be recognized that the TiO2 NTs/CeO2 photocatalyst would exhibit excellent potential in dyeing and electroplating wastewater purification and new energy development because of the attractive photocatalytic capacity.